Quantum chemical investigations of the water exchange mechanism on [Al III(H2O)5(L)]2+ as a function of the donor strength of the anionic L - Weber, Immo; Hanauer, Hans; Puchta, Ralph; van Eldik, Rudi; et al. (Journal of Molecular Modeling, 2014)
Water exchange reactions of the complexes [Al(H2O) 5L]2+·H2O for L = →OCN-, F-, CF3-, →NC-, →CN -, Cl-, Br-, H-, SH-, OH-, →NCO-, →NCS-, →SCN -, CF3CH2-, CH3 -, Et-, i-Pr- and t-but-, were studied by DFT calculations (B3LYP/6-311+G**). The reactions follow a dissociative (D) pathway for [Al(H2O)5L] 2+·H2O to form the five-coordinate intermediate [Al(H2O)4L]2+·2H2O for the weaker donor ligands of the series. On increasing the donor strength of L, the five-coordinate intermediate becomes significantly more stable than the reactant state. At this point there is a mechanistic changeover to an associative (A) pathway for [Al(H2O)4L]2+·2H 2O as reactant to form a six-coordinate intermediate [Al(H 2O)5L]2+·H2O. For some of the anionic ligands L = → NC-, →CN-, Cl -, OH- and →SCN-) the energy gap between the reactant and intermediate states is small, such that the water exchange mechanism lies in the boarder of dissociative and associative pathways. The water exchange process involves cis- and trans-orientated transition states to form the product state that is similar to the reactant state. © 2014 Springer-Verlag.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Aluminum; Anionic ligands; DFT calculations; Water exchange mechanism